Comparison of High Fluorescence Cell in Pediatric Patients with Acute Lymphoblastic Leukemia (ALL) and Infection - Raden Sindhi Triagustin Kusuma Menthari; Malayana Rahmita Nasution; Ricke Loesnihari; Nindia Sugih Arto; Ranti Permatasari; Dewi Indah Sari Siregar` (Indonesian Journal of Global Health Research, 2026)
High Fluorescence Cell (HFC) is a cell with high nucleoplasmic and nucleic acid content, enabling it to emit a high fluorescent signal. Mind Ray Series BC 760 automated hematology analyzer uses a technology called Sheath Fluid (SF) Cube to detect these cells using the fluorescence staining method. An increase in HFC may be associated with atypical or pleomorphic lymphocytes caused by viral infection rather than immature or monomorphic lymphocytes caused by malignancy. Objective: The objective of this study is to determine the difference in high fluorescence cell in pediatric patients with Acute Lymphoblastic Leukemia (ALL) and infection at Adam Malik Hospital. Methods: This study is an observational analytical study with a prospective cohort design. The study sample was 35 people with a diagnosis of ALL of 15 people and infection of 20 people. This study was conducted on patients who came to the pediatric clinic and were hospitalized with a diagnosis of ALL and infection at Adam Malik Hospital who met the inclusion criteria and agreed to participate in this study. A high fluorescence cell blood test was performed.  criteria. A complete blood test of 2 ml of blood in an EDTA vacutainer was gently homogenized. Analysis with a full blood count (FBC) test was performed using an automated hematology analyzer (Mindray BC 760) to obtain the number of lymphocytes and high fluorescence cells. Descriptive statistical analysis was used for demographic data. Statistical analysis used the Mann Whitney statistical test. The research data were analyzed statistically with the help of SPSS and the difference was considered significant if p value <0.05. Results: From the study sample of 35 people, 24 boys (68.6%) and 11 girls (31.4%), with the mean age of 6 years old. The diagnosis of ALL was 15 people (42.9%) while patients with infection were 20 people (57.1%). The median absolute HFC  in ALL was 0.2 x 109/L, and the median in infection was 0.15 x 109/L. Conclusion: There was no significant difference between HFC in patients with ALL and infection (p=0.211).